Isolation, Characterization of Neurospora crassa Mutants Exhibiting Growth Inhibition and Mutagenesis of this Fungus by the Leaf Extracts of Leucas aspera (Willd) Link - Bhuiyan, M Nazrul Islam; Mozmader, TIMA; Hoque, M Amirul; Akter, Sumi; Mahmud, Jahedul Islam (Bangladesh Journal of Scientific and Industrial Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Ten Neurospora crassa mutants obtained by chemical mutagenesis were screened in Leucas aspera (willd) Link. (Bengali name- swetadrone) plants. The aqueous extracts of the leaves of L. aspera showed significant inhibition of growth and mutagenic effect on N. crassa. Results showed that 1 ml extract reacted with the test organism of N. crassa very rapidly. During the period of 24 hours, it produced only 2.6 cm linear vegetative growth of the mycelia. Whereas, 1 ml and 0.50 ml extracts exhibited mild reactions (3.20 and 3.90 cm. respectively). The linear growth decreased with the increase of the concentrations of extracts. Conidia of Ema (5297) of N. crassa were treated for 3-4 hours in 100% concentration of the extracts. 100% extracts produced ten types of mutants, namely- dirty, vigorus, ropy, albino, mat, plug, check, fluppy, cauliflower and conidial brand. Key words: Neurospora crassa, Leucas aspera, Mutants, Dirty, Vigorous, Cauliflower and Conidial brand. Â DOI = 10.3329/bjsir.v43i3.1155 Bangladesh J. Sci. Ind. Res. 43(3), 387-396, 2008